2005
DOI: 10.1055/s-2004-830156
|View full text |Cite
|
Sign up to set email alerts
|

Gemeinsamkeiten der allergischen Rhinitis und des allergischen Asthma bronchiale?Die „One-Airway-One-Disease”-Hypothese

Abstract: ZusammenfassungImmunologische, genetische und epidemiologische Ergebnisse weisen auf eine sehr enge Beziehung zwischen der allergischen Rhinitis und dem allergischen Asthma bronchiale hin. Diese Aspekte wurden im Teil 1 dieser Übersicht dargestellt. Im Teil 2 werden die Klinik und Diagnostik insbesondere aber gemeinsame Therapieansätze vorgestellt. Die Allergenkarenz bildet bei allergologischen Erkrankungen das erste und wichtigste therapeutische Standbein. Die spezifische Immuntherapie (SIT), Leukotrien-modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…A number of studies have suggested that children who suffer from allergic rhinitis are three times more likely to develop adult-onset asthma [7, 8]. Results of other investigations indicate that about 80% of patients with allergic asthma also suffer from symptoms of allergic rhinitis [9].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that children who suffer from allergic rhinitis are three times more likely to develop adult-onset asthma [7, 8]. Results of other investigations indicate that about 80% of patients with allergic asthma also suffer from symptoms of allergic rhinitis [9].…”
Section: Introductionmentioning
confidence: 99%